Hubungan Kualitas Fisik Rumah Dengan Kejadian TBC Paru Di Wilayah Kerja Puskesmas I Denpasar Selatan Tahun 2018 - Ni Komang Suari Melinda Dewi; Anysiah Elly Yulianti (Jurnal Kesehatan Lingkungan (JKL), 2019)
Indonesia is the second country with the highest population of Tuberculosis in the world after India. Tuberculosis is caused by Microbacterium tuberculosis wich transmitted through the airborne. One of the efforts for prevent the TBC transmitted is keeping the healthy quality physical of home. This research purposed to know the correlation between quality physical of home with lung TBC case at Puskesmas I South Denpasar working area. The types of this research is observasional retrospektif using case control design. Sampling procedures using total population sampling technique. The case group sample amount 34 patient with TBC in 2016 at Puskesmas I South Denpasar. The control grup sample amount 34 people who never suffer lung TBC and has same characteristics with the case group sample. Data collection using observation paper and analys statistic test using chi square method, continued with counting Coefficient Contigency (CC). Based on the chi square method result, showing the relation between lighting (p=0,001 CC=0,361), ventilation (p=0,014 CC=0,286), humadity (p=0,013 CC=0,290) dan temperature (p=0,000 CC=0,246) of home with lung TBC. There are no relation between the number of occupants home (p=0,086) and wall floor quality’s (p=0,088) with lung TBC case. Submitted suggestion in this research are 1) for community, please keep your attention for healthy and hygiene home, 2) for Puskesmas I South Denpasar, should be increased the health promotion about health housing wich related with Lung TBC.